Role of Alginate O Acetylation in Resistance of Mucoid Pseudomonas aeruginosa to Opsonic Phagocytosis - Pier, Gerald B. (American Society for Microbiology, 2001)
Establishment and maintenance of chronic lung infections with mucoid Pseudomonas aeruginosa in patients with cystic fibrosis (CF) require that the bacteria avoid host defenses. Elaboration of the extracellular, O-acetylated mucoid exopolysaccharide, or alginate, is a major microbial factor in resistance to immune effectors. Here we show that O acetylation of alginate maximizes the resistance of mucoid P. aeruginosa to antibody-independent opsonic killing and is the molecular basis for the resistance of mucoid P. aeruginosa to normally nonopsonic but alginate-specific antibodies found in normal human sera and sera of infected CF patients. O acetylation of alginate appears to be critical for P. aeruginosa resistance to host immune effectors in CF patients.